Sunny Uppal IPCC WGIII release event April 16 2014 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Catalyzing mitigation through the Climate and Clean Air Coalition (CCAC) -- Sunny Uppal, Environment Canada, CCAC Meeting global food needs with lower emissions: IPCC report findings on climate change mitigation in agriculture A dialog among scientists, practitioners and financiers April 16, 2014 World Bank, Washington, DC